Fractionated semen collection as a tool to rescue fertility in stallions with seminal vesiculitis - Oliveira, Sidnei N. [UNESP]; Andrade, Luiz R.P. [UNESP]; Silva, Luis F.M.C. [UNESP]; Araujo, Endrigo A.B. [UNESP]; Rayashi, Rafaella M. [UNESP]; Segabinazzi, Lorenzo G.T.M. [UNESP]; Alvarenga, Marco A. [UNESP]; Dell'Aqua, Camila PF. [UNESP]; Dell'Aqua, Jose A. [UNESP]; Papa, Frederico O. [UNESP] (Elsevier, 2020)
Treatments for seminal vesiculitis have poor outcomes in stallions; thus, the development of alternative strategies is warranted. This study aimed to evaluate fractionated semen collection as a method to restore the fertility of stallions diagnosed with seminal vesiculitis. Eighteen ejaculates from six stallions (three ejaculates/stallion) diagnosed with seminal vesiculitis were harvested in fractions, as follows: Fraction A (FA), the first two jets; Fraction B (FB), the third and fourth jets; and Fraction C (FC), the fifth and remaining jets of the ejaculate. All fractions were subject to standard semen evaluations that were performed in addition to cytology and bacterial aerobic cultures. Fractions were extended and cooled to 5 °C. As a proof of concept, 20 mares (48 estrous cycles, ∼8 cycles/stallion) were bred with 1 billion sperm from FA (cooled at 5 °C for 24 h). In our study, FA had negative bacterial cultures, absent macroscopic or microscopic abnormalities; FB had positive bacterial cultures in two stallions and presence of polymorphonuclear neutrophils (PMNs) in all samples, but with no macroscopic abnormalities; and FC had positive bacterial cultures, purulent appearance, and the presence of degenerated PMNs, just as noted in the whole semen. Overall, post-cooling sperm motility results were superior (P < 0.05) for FA in comparison with FB and FC. First cycle pregnancy rates using FA varied from 66% to 86%. None of the non-pregnant mares developed endometritis. In conclusion, fractionated semen collection can be used to obtain semen free of contamination and to achieve satisfactory pregnancy rates from stallions with seminal vesiculitis.
Keywords: Cooled semen; Horse; Infertility; Pyospermia; Sperm